Human bite cases reported to health facilities in the Volta region of Ghana, 2019 to 2023 - Kubio, Chrysantus; Afetor, Maxwell; Bosoka, Samuel Adolf; Abanga, Williams Azumah; Zeng, Victor; Tamal, Christopher Sunkwa; lssahaku, Gyesi Razak; Narh, Clement Tetteh; Baiden, Frank (Frontiers in Public Health, 2025)
IntroductionAlthough human bite injuries occur less frequently than other types of injuries, they present notable public health challenges, yet they have received relatively little attention. This study examined the incidence, trend, and distribution of human bite injuries in the Volta Region of Ghana from 2019 to 2023.MethodA retrospective analysis of human bite injury data from the District Health Information Management System 2 (DHIMS-2) for the Volta Region was conducted for the period 2019 to 2023. Data on human bite injuries were obtained from the monthly outpatient (OPD) morbidity report form. Variables available and extracted were age, sex, district and year of report. The data was analyzed descriptively using Microsoft Excel and Quantum Geographic Information System (QGIS) and the findings presented in tables and graphs.ResultA total of 931 human bite injuries were reported to health facilities from 2019 to 2023, with the highest incidence of 12.0 per 100,000 recorded in 2021 and the lowest, 9.7 per 100,000 in 2019. Males and young adults between the ages of 18–34 accounted for 58.1 and 41.1%, respectively of all cases reported. Geographically, Ketu North recorded the highest number of cases, 184 (19.8%). There we no reported death due to human bite.ConclusionHuman bite injuries in the Volta Region have shown an upward trend over the years studied, with males and young adults aged 18 to 34 years affected in the majority of the reported cases. While the causes and infection outcomes were not determined, this study provides essential baseline data for further research into the causes and effects of these injuries.